Implementasi Profil Pelajar Pancasila Dalam Satua Bali: Membentuk Karakter dan Moderasi Beragama Pada Anak - Parta, Ida Bagus Made Wisnu; Aryasuari, I Gusti Ayu Putu Istri (Jurnal Penelitian Agama Hindu, 2025)
Satua is a Balinese traditional fairy tale or literary work in prose that contains life values, one of which is Satua Tong! Ceng! Pung! Pung! Jir! as the object of research. The purpose of this study is to determine whether Balinese satua can educate children's character and foster a sense of religious moderation in Bali. This study uses transformation theory, sociological theory, and ethnopedagogy theory supported by analytical descriptive methods and reading techniques in analyzing data. The results of this study are (1) revitalizing Balinese language satua by transforming books into learning videos that contain the values ​​of the Pancasila student profile dimensions. (2) There are three basic frameworks of Hinduism in satua, including: (a) Tatwa (philosophy) there are five philosophies of faith as the basis of belief called Panca Sradha, (b) Susila (ethics) there are Tat Twam Asi and Tri Kaya Parisudha which emphasize the attitude of mutual belonging and feeling as fellow living beings. (c) Ceremony (ritual) there is a sincere holy sacrifice called Yadnya which consists of five parts called Panca Yadnya. (3) Based on the responses of teaching teachers and the responses of 161 students from 9 elementary schools in Bali, 20.36% chose neutral, 49.87% agreed, and 29.76% strongly agreed. Thus, the use of learning video media can increase students' interest in learning and shape children's character according to the profile of Pancasila students, as well as foster an attitude of religious moderation in Bali.